A Journey towards English Language Reform in a Malaysian TVET Institution - Puteh Behak, Fariza; Mat Saad, Noor Saazai; Darmi, Ramiaida; Selamat , Suzanah; Ishak, Maziahtusima (Al-Azkiyaa - International Journal of Language and Education, 2025)
This article explores the English language reform carried out by the Seroja Technical Group of Colleges (STC) in accordance with the English Language Education Reform in Malaysia: The Roadmap 2015-2025. This article specifically intends to examine the affordances and limitations encountered by STC lecturers in implementing the English language reform initiative. This research project is a component of a broader study that employed a concurrent mixed method approach, integrating both quantitative and qualitative data. The paper's discussion focuses on data obtained from the qualitative component of the inquiry. The study was carried out at STC, a group of TVET institutions that is actively aiming for making English as one of the primary instructional languages. The participants of the study were 10 technical lecturers from STC. The data collection method was semi-structured interviews . The data was subsequently transcribed and categorized and subsequently organized into meaningful themes. Thematic analysis was employed to analyze the data. The findings indicate that STC's endeavours to reform the English language have achieved a moderate level of success, as the language is effectively integrated into teaching and learning practices, classroom resources, and teacher-student interactions. Nevertheless, the data also indicates that the lecturers encountered difficulties in properly implementing the strategy as a result of students' backgrounds and other situational considerations. Ultimately, the lecturers employed a contextualized strategy to accomplish the policy objectives. The results of this study are advantageous for policymakers and practitioners in reorganizing the English language at their institutions.